Fabrication and Physiochemical Properties of Chitosan and Fish Gelatin Biofilm for Wound Healing Process - JIVAAN DEVENDRAN; Dr. MAIZLINDA IZWANA BINTI IDRIS (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study explores the development and characterization of a chitosan/fish gelatin biofilm for wound healing applications. Chronic wounds are a growing healthcare concern, especially among elderly and immuno-compromised patients. Conventional synthetic wound dressings often lack biocompatibility and sustainability, highlighting the need for bio-based alternatives. Chitosan, known for its biodegradability, biocompatibility, and antibacterial properties, was combined with fish gelatin, recognized for its compatibility with living tissue and wound-healing potential. The biofilms were fabricated using a solution casting method with varying ratios of chitosan and fish gelatin (100:0, 95:5, 90:10, 85:15 and 80:20) and cross-linked with glutaraldehyde to enhance mechanical stability. Physiochemical properties of the biofilms were analyzed using Fourier Transform Infrared Spectroscopy (FTIR), Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), and contact angle measurements. Fourier Transform Infrared Spectroscopy (FTIR) confirmed successful blending and cross-linking, as evidenced by characteristic peaks associated with amide and hydroxyl groups. Scanning Electron Microscopy (SEM) revealed a homogeneous surface morphology with improved structural integrity as fish gelatin content increased. Atomic Force Microscopy (AFM) showed a reduction in surface roughness, with the root mean square roughness (Rq) decreasing from 64.033 nm in the CH biofilm to 2.546 nm in the CHCF20 biofilm, indicating improved smoothness and compatibility for wound healing. Contact angle measurements indicates that the material is hydrophilic, as evidenced by the significant reduction in contact angles from 87.03° to 83.03° and further to 67.4° with increasing gelatin ratio, showcasing its ability to retain moisture and support healing. This study successfully demonstrates the potential of chitosan/fish gelatin biofilm as an effective, biocompatible, and environmentally sustainable wound dressing.